Response Time and Patient Satisfaction in Islamic Hospital: A Cross Sectional Study - Dilgu Meri; Aris Citra Wisuda; Rifa Yanti; Riski Novera Yenita (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Timely delivery of emergency services is a critical priority in healthcare systems worldwide, with both speed and accuracy in patient care serving as essential indicators of service quality. This study investigates the relationship between nurses' response time and patient satisfaction in the emergency department of Ibnu Sina Islamic Hospital, Pekanbaru. A quantitative, cross-sectional design was employed from December 2023 to July 2024. The study population consisted of family members accompanying patients to the emergency department. Using accidental sampling and the Slovin formula, a total of 94 participants were selected. Data were analyzed using the Chi-Square statistical test. Among the respondents, 83 individuals (88.3%) rated the response time as fast, while 11 (11.7%) perceived it as slow. In terms of satisfaction, 72 respondents (76.6%) reported being satisfied, whereas 22 (23.4%) expressed dissatisfaction. Chi-Square analysis revealed a statistically significant association between response time and patient satisfaction (p = 0.003, p < 0.05), indicating that faster response times are positively correlated with higher levels of patient satisfaction in the emergency department. Keywords: Nurse, Response Time, Patient Satisfaction, Emergency Department, Hospital.